Implementation of the D’PEk_Hil for Early Detection of Preeclampsia and Clinical Recommendations in Pregnant Women - Viola Violentina; Melyana Nurul W; Arwani; Umi Toifah; Khairulisni Saniati (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Early detection and the management provide strategic role to decide therapies for mothers with high risk of preeclampsia and to prevent further complication. Expert-consulting system-based application could accelerate the early detection of preeclampsia and provides immediate expert feedbacks. This research and development attempted to implement D’PEk_Hil application for early detection and provide preeclampsia recommendation. This quasi-experimental design used posttest only design with non-equivalent control group. The subjects were 28 midwives grouped into intervention group to receive D’PEk_Hil application, consisting of 14 midwives; and control group to receive Mother-Child handbook, consisting of 14 midwives. The researchers analyzed the data with independent t-test. D’PEk_Hil application, observed in the intervention group, yieleded an immediate diagnose provision with 435,46 ± 25,809 (seconds) while the control group was with 608,11 ± 62,756 (seconds), (p-value of 0.01). The intervention group had a speed of providing recommendation for 444,46 ± 25,809 (seconds) while the control group was 695,25 ± 62,756 (seconds), (p-value of 0.000). The results revealed significant mean differences of diagnosis provision speed and in terms of providing recommendation based on the diagnoses between the groups. The D’PEk_Hill implementation could improve the time efficiency to early detect and provide therapy recommendaitons for preeclampsia mothers.